2020
DOI: 10.3390/antiox9040344
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanisms of Action of Natural Antioxidants in Health and Disease

Abstract: Natural antioxidants have been proposed to have beneficial effects on health and on different disease states, such as neurodegenerative and cardiovascular diseases, diabetes and cancer [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 30 publications
0
32
0
4
Order By: Relevance
“…Nevertheless, a polyphenol-rich diet has beneficial effects on health and diseases associated with freeradical pathological mechanisms, like diabetes, obesity, cancer, cardiovascular, and neurodegenerative diseases. Their mode of action may be related to mediation of interactions with specific proteins central to intracellular signaling cascades, modification of the expression and activity of key proteins, modulation by epigenetics modifications, or impact on the gut microbiota [120]. Vulganova et al [71] reported the significant inhibitory activity of methanolic extract of dried leaves of S. apiana against 4 selected serine proteinases: trypsin, thrombin, urokinase, and plasmin.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Nevertheless, a polyphenol-rich diet has beneficial effects on health and diseases associated with freeradical pathological mechanisms, like diabetes, obesity, cancer, cardiovascular, and neurodegenerative diseases. Their mode of action may be related to mediation of interactions with specific proteins central to intracellular signaling cascades, modification of the expression and activity of key proteins, modulation by epigenetics modifications, or impact on the gut microbiota [120]. Vulganova et al [71] reported the significant inhibitory activity of methanolic extract of dried leaves of S. apiana against 4 selected serine proteinases: trypsin, thrombin, urokinase, and plasmin.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Several molecular mechanisms have been proposed to explain the biological functions of flavonoids. According to the oldest, but highly controversial view, flavonoids would exert their effects by free-radical scavenging [ 16 , 18 , 19 ], which is proportional to the redox potential of these molecules, usually correlating with the number of hydroxyl groups [ 20 , 21 , 22 ]. However, the last two decades have provided more convincing explanations of antioxidant effects of flavonoids, which suggest that these compounds (i) interact with specific proteins central to signaling cascades and modulate the activity and/or expression of key antioxidant proteins; (ii) influence the epigenetic mechanisms of gene expression; and (iii) modulate the gut microbiota profile and metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…However, the last two decades have provided more convincing explanations of antioxidant effects of flavonoids, which suggest that these compounds (i) interact with specific proteins central to signaling cascades and modulate the activity and/or expression of key antioxidant proteins; (ii) influence the epigenetic mechanisms of gene expression; and (iii) modulate the gut microbiota profile and metabolites. Thus, while the current view is that pleiotropic mechanisms contribute to the final beneficial effect of polyphenols [ 21 , 22 ], the role of specific flavonoid–protein interactions is increasingly recognized [ 23 ]. A well-recognized direct target of polyphenols are phosphodiesterases (PDEs).…”
Section: Introductionmentioning
confidence: 99%
“…The PFA also prevents peroxide formation by modifying the activities of antioxidant enzymes. Moreover, they can interact with specific proteins and modulate their expression and activities [ 11 ]…”
Section: Introductionmentioning
confidence: 99%